2019
DOI: 10.1021/acs.chemrestox.9b00013
|View full text |Cite
|
Sign up to set email alerts
|

(De)Toxifying the Epigenetic Code

Abstract: Cells are continuously subjected to an array of reactive/toxic chemical species which are produced both endogenously through metabolic pathways and taken up exogenously by diet and exposure to drugs or toxins. As a result, proteins often undergo non-enzymatic covalent modifications (NECMs) by these species, which can alter protein structure, function, stability, and binding partner affinity. NECMs accumulate over time and are linked to various diseases such as Alzheimer's disease, cancer, and diabetes. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 90 publications
0
23
0
Order By: Relevance
“…Lys acetylation, like many PTMs, is regulated enzymatically through the addition (Lys acetyltransferases) and removal (Lys deacetylases) of the acetyl group (Zhao et al, 2010). While most PTMs are tightly regulated, there is growing interest in non-enzymatic PTMs and their role in metabolic regulation and cell homeostasis (Moellering and Cravatt, 2013;Zheng et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%
“…Lys acetylation, like many PTMs, is regulated enzymatically through the addition (Lys acetyltransferases) and removal (Lys deacetylases) of the acetyl group (Zhao et al, 2010). While most PTMs are tightly regulated, there is growing interest in non-enzymatic PTMs and their role in metabolic regulation and cell homeostasis (Moellering and Cravatt, 2013;Zheng et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the most well-characterized histone modifications are enzymatic, in the past few years it has become clear that histones are also prime substrates of nonenzymatic covalent modifications that induce changes in chromatin structure and function 17 . We recently found that core histones are subjected to MGO glycation and that these adducts change chromatin architecture, the epigenetic landscape, and transcription, and particularly accumulate in disease states 18,19 .…”
mentioning
confidence: 99%
“…Several protein systems have previously been described as being capable of intercepting reactive metabolites and byproducts both in the cytosol and in the nucleus before they can reach the histones (Figure 3A). In addition to the glyoxalase cycle mentioned earlier, aldehyde and lactate dehydrogenases utilize NAD + as a cofactor and directly oxidize aldehyde and lactate molecules into their respective less deleterious carboxylates [51,52]. Conversely, aldo-keto reductases use NADPH as a cofactor to reduce aldehydes into alcohols, which are more easily managed [53].…”
Section: Cellular Defense Mechanisms Against Necmsmentioning
confidence: 99%